Human atrial natriuretic factor and renin-aldosterone in paracetamol induced fulminant hepatic failure. Issue 1 (January 1991) - Panos, M Z; Anderson, J V; Forbes, A; Payne, N; Slater, J D; Rees, L; Williams, R
Abstract : It has been postulated that deficiency of a putative natriuretic factor, or resistance to such a factor, may contribute to sodium retention in fulminant hepatic failure. Levels of plasma human atrial natriuretic factor (h-ANF), plasma renin activity, and aldosterone concentration were measured in 33 patients with fulminant hepatic failure due to paracetamol overdose, and 12 healthy control subjects. Levels of h-ANF were raised only in patients with evidence of severe renal impairment (serum creatinine greater than 300 mumol/l and urine output less than 100 ml/24 hours). h-ANF values were median 4.15, range 2-9 pmol/l and 10.1, 1-25 pmol/l for the control and severe renal impairment groups respectively (p less than 0.001). In the latter plasma renin activity was raised compared to that in control subjects (median 19.8, range 1.04-41.7 and 2.86, 1.87-5.9 pmol/l/h respectively, p less than 0.02). Plasma aldosterone concentration was also raised in patients (2176, 199-6894 pmol/l compared to 368, 133-578 pmol/l in control subjects, p less than 0.01). Haemodialysis induced changes in circulating h-ANF which correlated with volume and right atrial pressure changes (p less than 0.001 and p less than 0.05 respectively). In six patients with no or mild renal failure infusion of 900 ml 5% human albumin solution caused a significant increase in plasma h-ANF (p less than 0.05) without natriuresis or diuresis, a finding compatible with the hypothesis that there may be resistance to h-ANF in this group. The present findings indicate that there is no deficiency of h-ANF in fulminant hepatic failure and that known mechanisms of h-ANF release are not impaired.